TRADITIONAL LEARNING OF THE AWAMEL BOOK IN DAYAH DARUL ULUM ABU LUENG IE, ACEH BESAR: TRADISI PEMBELAJARAN KITAB AWAMEL DI DAYAH DARUL ULUM ABU LUENG IE ACEH BESAR - Nurjannah, Nurjannah; Matsyah, Ajidar; Ruhamah (Indonesian Journal of Islamic History and Culture, 2023)
This research aims to explore the tradition of learning the Awamel book in Dayah Darul Ulum Abu Lueng Ie, Aceh Besar. This book is a fundamental key to understanding other kitab kuning, making it a mandatory study for students. The Awamel book, or Nahwu, is a crucial branch of knowledge in Arabic grammar that significantly influences or determines the words that follow it. This study employs qualitative research methods. The research results reveal that the tradition of learning the Awamel book has been ongoing from the past to the present, serving as a fundamental element in every Dayah, especially Dayah Darul Ulum Abu Lueng Ie. The study shows that the book is mandatory for students to learn, as it is essential for understanding the content of kitab kuning. Learning the Awamel book is a crucial material that students must go through to comprehend the Arabic language and plain Arabic-scripted books. To achieve success, a method is employed to study the Awamel book, focusing on discussing its principles and providing examples to facilitate students' understanding. In addition to this method, efforts are made to maximize students' learning outcomes by assigning tasks and evaluations aimed at determining the extent to which students understand the book's content.